The Role of Antioxidants as Adjuvants of Fibromyalgia Management - Sabrina Chusnul Chotimah; Hamzah Shatri; Rudi Putranto; Edward Faisal; Vinandia Irvianita; Yanuar Ardhani; Dika Sinulingga (Indonesian Rheumatology Association, 2023)
Fibromyalgia is a condition with complex polysymptomatology characterized by chronic widespread pain, fatigue, sleep disturbances, and functional symptoms. Oxidative stress plays a role in the etiology of pain which is the main symptom of fibromyalgia. The symptoms of fibromyalgia are related to the balance of oxidant and antioxidant. Antioxidants from certain nutrients can act to counter the high level of free radicals, in order to maintain the oxidative stress/antioxidant balance. Antioxidant such as coenzyme Q10, vitamin C and E, magnesium, and acetyl-L-carnitine have the potential benefit as adjuvants in treating fibromyalgia by reducing pain.